VII South-Eastern Europe Symposium on Vegetables & Potatoes (University of Maribor Press, 2017)
University of Maribor Faculty of Agriculture and Life Science and the International Society of Horticulture Sciences (ISHS) with the support of Food and Agriculture Organization (FAO) and Slovene Ministry of Agriculture, Food and Forestry (MAFF) have the honor to welcome all engaged in research, development, producers, teaching, extension and public services, suppliers of horticulture materials, cooperatives, private sector and stakeholders related to vegetable and potatoes production to attend the 7th South East European (former Balkan) Symposium on vegetables and potatoes. The Symposium is held in Maribor (university city and in 2012 European culture capital) in the north East of Slovenia from where comes the majority of agriculture products including vegetables as along the river Drava several irrigation systems were established. Long tradition of vegetable production for processing industry in the past and for fresh market in the last period, encouraged Slovene Association for integrated vegetable production established in the year 2000, to prepare all procedures for the first vegetable crop with the origin of denomination “Ptujski lük” which was approved on the European level on 2011. Two days of symposium from 20th to 23rd of June 2017 have scientific programme with additional FAO workshop on GAP for Greenhouse Production on small farms in SEE with the presentation of a new manual printed by FAO in 2017, ISHS meeting and special session about possibilities for networking among researchers in the future. Scientific programme is covering topics: Production systems and quality of V&P, Organic V&P production, Short supply chains and other concepts of V&P marketing, Protected cultivation and GAP of greenhouse production on small farms, Biodiversity, Irrigation and plant water relations, Genetic resources and breeding, Potato, Plant protection, General and other topics. On the 22nd of June 2017 a side event for vegetable and potatoes growers, advisors, technical workers and other professional public titled ”Some important facts for improving greenhouse vegetable production” will take place. Under support of FAO and MAFF ten distinguished professionalists will present the most important topics for successful greenhouse vegetable production with the goal to give also Slovene growers and professional public insights in novel research findings and recommendations for improvements. Last day is field trip to growers where different production methods (from biodynamic organic to integrated and soilless, Global GAP) and different marketing strategies (direct selling, CSA, protected origin products, establishing non formal cooperation’s and supplying to big chains) are presented with the aim to exchange ideas and knowledge among participants and growers from Podravje region. We hope that you will have a nice time in Slovenia and enjoy your stay with us – a team from Chair of Organic Agriculture, Field Crops, Vegetable and Ornamental Plants University of Maribor Faculty of Agriculture and Life Science.